Research Trends in the Application of Problem Based Learning Model in chemistry learning in Indonesia: A Systematic Literature Review - Muhammad Habib Ash Shiddiqi; Purwaningsih , Dyah; Pujiana, Elma (Universitas Islam Indonesia, 2025)
This study aims to analyze and map research trends on the application of the Problem-Based Learning (PBL) model in chemistry education in Indonesia using the systematic literature review (SLR) method. The study involved secondary data sourced from the SINTA database for publications between 2015 and 2024. Articles were identified using the keywords